ISSUES IN TRANSLATION OF BALINESE CULTURAL TERMS INTO ENGLISH - Kadek Putri Yamayanti (Universitas Kuningan, 2020)
This descriptive qualitative study investigates translation equivalent of Balinese cultural terms into English. It is based on the understanding that cultural terms belong to salient part in dealing with translation due to the cultural gap between source and target languages. Therefore, this study is conducted in order to find out the degree of equivalence between Balinese cultural terms and their translations into English in the book entitled Memahami Roh Bali Desa Adat sebagai Ikon Tri Hita Karana and its translation in Discovering the Spirit of Bali Customary Village as Icon of Tri Hita Karana. In finding the degree of equivalence, componential analysis especially the binary features was applied in terms of confirming the semantic features. The result showed that all translated cultural terms have no exact synonymy into source language. Some semantic features do not occur in target language as a result of lack terms in target language. The translator tends to replace cultural terms in source language into appropriate terms in target language based on his knowledge and experiences even in some cases, it shows the loss and gain information. However, overall, those translated cultural terms still can share some basic semantic features of the source language. Keywords: cultural term; semantic features; equivalence.